The diversity of mycorrhizal fungi in Japanese Cephalanthera species. Issue 1 (14th January 2016) - Sakamoto, Yuki; Yamazaki, Jun; Yamada, Takayuki; Yokoyama, Jun; Ogura‐Tsujita, Yuki; Maki, Masayuki
Abstract: The diversity of mycorrhizal fungi among four Japanese C ephalanthera (Orchidaceae) species was examined at a total of seven sites, based on sequence variation in nuclear ribosomal DNA. This is the first report to detect mycorrhizal fungi in C . subaphylla . Two patterns of mycorrhizal associations were confirmed from our results. C . falcata has lower fungal specificity, associating with Russulaceae, Sebacinales and Thelephoraceae. By contrast, the three C ephalanthera species C . erecta, C . subaphylla, and C . longifolia were associated mainly with Thelephoraceae fungi. There is no large difference found in mycobionts between green and albino individuals of C . falcata and no distinct preference of Japanese C ephalanthera species for a specific fungal group of Thelephoraceae. Abstract : Symbiotic mycorrhizal fungi were examined in four Japanese Cephalanthera . Two patterns of mycorrhizal associations were confirmed in the Cephalanthera . The Cephalanthera have no specific preferences to the symbiotic Thelephoraceae.